Studies on the inclusion of genetic resistance to gastrointestinal parasites in sheep breeding: Doctoral thesis abstract - Sanchez Batista, Ana Laura; Ponzoni, Raul Walter (Agrociencia Uruguay, 2023)
Parasitosis caused by gastrointestinal nematodes (GIN) limits sheep production in pastoral systems in Uruguay. The use of anthelmintics has led to nematode resistance to drenches. Selection for resistance to GIN has proven to be beneficial. Worm egg count per gram of faeces (WEC) is used to identify resistant sheep, but there is a lack of consensus on its accuracy and the number of animals to sample. Applying statistical theory, I found that 100 WEC is accurate enough, but the sample size used is inadequate. Defining resistance to GIN as a trait in the selection objective is not straightforward. There are two options for incorporating it into flocks: within- flock selection, and incorporation of genetically improved material. I used a desired gains approach to include resistance to GIN in a multi-trait selection objective in Merino sheep. The index initially used resulted in equal importance to wool and meat, and I gradually placed greater emphasis on resistance to GIN during selection. After 10 years, with a 25 % emphasis on resistance to GIN, I predicted a WEC reduction below the threshold of 500 WEC at low and medium infestations. With high infestations, an emphasis of 50 % or more was required, which negatively affected other production traits. In such cases, within flock selection would not eliminate the need to use anthelmintics in 10 years. Difficulties specific to selection for resistance to GIN and other constraints could result in lower gains than predicted. Genetic gain could be accelerated by selecting within and between flocks, taking advantage of efforts made by national as well as overseas breeders. Foreign sources have shown resistance to GIN locally without affecting production traits. Producers should use breeding values from genetic evaluations when acquiring rams, once they have decided on the emphasis to be placed on resistance to GIN.